OPTIMALISASI TEKNOLOGI 3D PRINTING PADA INOVASI PENGEMBANGAN MEDIA PEMBELAJARAN GURU MATEMATIKA KOTA PAREPARE - Irmayani, irmayani; Husain, Hartina; Zain, Abdul; Tahir, Sri Sukma; Sukardi, Sarah Nabila (Jurnal Abdi Insani, 2024)
The role of learning media in the learning and teaching process is an integral part of the world of education. The development of technology-based learning media in the field of mathematics has a great influence on students' level of understanding. 3D printing technology can stimulate teacher interest and creativity in creating learning media prototype objects. The aim of implementing this activity is to increase the knowledge and skills of Parepare City Mathematics Teachers in creating innovative technology-based spatial mathematics learning media which is able to increase students' interest in learning the material thereby improving student learning outcomes. Implementation methods include observation, discussion, lectures and practicum. The activities were carried out in several training series. Technology optimization training on innovation in learning media development, training and assistance on the use of Ultimaker cura software on mathematics learning media, and training and assistance on 3D printing machines as mathematics learning media. The results of this activity were an increase in understanding of learning media concepts from 37.5% to 92.5%. Partners have understood and are able to sketch three-dimensional learning media using the ultimaker cura software, this is indicated by the existence of new knowledge about the software from not knowing to being able to operate which has increased by up to 82.5%, partners understand and are able to operate the devices on the 3D Printing machine to produce three- dimensional learning media that are suitable for use and this is proven by the survey figures for increasing knowledge by up to 87.5% and the ability of partners to color learning media which has increased by up to 87.5%. The survey results show that after the training and mentoring activities, knowledge and skills have increased significantly. The conclusion from the implementation of this activity is that training participants have been able to create innovative learning media that can increase students' enthusiasm for learning so that there is an increase in student learning outcomes.